Invited: Wireless sensor nodes for environmental monitoring in Internet of Things - Lu, Ting-Chou; Huang, Li-Ren; Lee, Yu; Tsai, Kun-Ju; Liao, Yu-Te; Cheng, Nai-Chen; Chu, Yuan-Hua; Tsai, Yi-Hsing; Chen, Fang-Chu; Chiueh, Tzi-Cker (My University, 2016)
This paper presents a self-sustainable landslide surveillance system that detects hazardous water content level in soils and provides real-time landslide warnings to residents, without requiring wired electricity transmission. A self-powered soil water content sensor was applied as the trigger of alert event. It solves the energy supply problem by an environmental interrupt mechanism, which wakes up the sensor and communication circuits in a sensing node only when the water content in monitored soils exceeds a certain threshold, and thus completely eliminates the need for an ALS node to periodically wake up, sense and communicate. By tightly integrating energy harvesting, environment sensing and circuit wake-up, it may well be the most energy-efficient landslide surveillance system designed to monitor water content in soils in the world.
Keywords: Renewable energy; soil battery; energy harvesting; wireless monitoring; smart sensing; soil moisture